Study on the process of intervertebral disc disease by the theory of continuum damage mechanics. (August 2022) - Cui, Yangyang; Shen, Hangkai; Chen, Yuru; Zhang, Wei; Zhu, Jia; Duan, Zhili; Liao, Zhenhua; Weiqiang, Liu
Abstract: Background: Recently, more and more people suffer from low back pain triggered by lumbar degenerative disc disease. The mechanical factor is one of the most significant causes of disc degeneration. This study aims to explore the biomechanical responses of the intervertebral disc, and investigate the process of disc injury by the theory of continuum damage mechanics. Methods: A finite element model of the L4–L5 lumbar spine was developed and validated. The model not only considered changes in permeability coefficient with strain, but also included physiological factors such as osmotic pressure. Three loading conditions were simulated: (A) static loads, (B) vibration loads, (C) injury process. Findings: The simulation results revealed that the facet joints shared massive stresses of the intervertebral discs, and prevented excessive lumbar spine movement. However, their asymmetrical position may have led to degeneration. The von Mises stress and pore pressure of annulus fibrosus showed significantly different trends under static loads and vibration loads. The von Mises stress of nucleus pulposus was not sensitive to vibration loads, but its pore pressure was conspicuously influenced by vibration loads. The injury first appeared at the posterior centre, and then, it gradually expanded along the edge of the intervertebral disc. With an increase in the loading steps, the damage rate of the intervertebral disc increased logarithmically. Interpretation: The variation in the biomechanical performance of the intervertebral disc could be attributed to the periodic movement of internal fluids. This study might be helpful for understanding the mechanism of intervertebral disc degeneration. Highlights: The injury process of the intervertebral disc was investigated. The injury first appeared at the posterior center, and then gradually expanded along the edge. The mechanical response of the lumbar intervertebral disc was investigated. The fluid movement in the intervertebral disc was studied. The damage rate increased logarithmically with an increase in loading steps.